Sacred Views of Saint Francis The Sacro Monte di Orta - Ho, Cynthia O. (punctum books, 2020)
Overlooking Lago di Orta in the foothills of the Northern Italian Alps, the Renaissance-era Sacro Monte di Orta (a UNESCO World Heritage site) is spectacle and hagiography, theme park and treatise. Sacro Monte di Orta is a sacred mountain complex that extolls the life of St. Francis of Assisi through fresco, statuary, and built environment. Descending from the vision of the 16th-century Archbishop Carlo Borromeo, the design and execution of the chapels express the Catholic Church's desire to define, or, perhaps redefine itself for a transforming Christian diaspora. And in the struggle to provide a spiritual and geographical front against the spread of Protestantism into the Italian peninsula, the Catholic Church mustered the most powerful weapon it had: the widely popular native Italian saint, Francis of Assisi.Sacred Views of Saint Francis: The Sacro Monte di Orta examines this important pilgrimage site where Francis is embraced as a ne plus ultra saint. The book delves into a pivotal moment in the life of the Catholic Church as revealed through the artistic program of the Sacro Monte's twenty-one chapels, providing a nuanced understanding of the role the site played in the Counter-Reformation.The Sacro Monte di Orta was, in its way, a new hagiographical text vital to post-Tridentine Italy. Sacred Views provides research and analysis of this popular, yet critically neglected Franciscan devotional site. Sacred Views is the first significant scholarly work on the Sacro Monte di Orta in English and one of the very few full-length treatments in any language. It includes a catalogue of artists, over one hundred photographs, maps, short essays on each chapel, and longer essays that examine some of the most significant chapels in greater detail.